It's not just 'What' you do, it's also the 'Way' that you do it: Patient and Public Involvement in the Development of Health Research. (16th January 2018) - Devonport, Tracey J; Nicholls, Wendy; Johnston, Lynne H; Gutteridge, Robin; Watt, Angela
Abstract: Purpose: This article presents a reflective account of Patient and Public Involvement (PPI) in the development of obesity and binge eating research. Method: We established Patient Advisory Groups (PAGs) at two English regional National Health Service (NHS) weight management services. PPI was evaluated as follows: (i) PAG members completed a Post Participation Evaluation Questionnaire, (ii) PAG meetings captured group discussion on PPI involvement, (iii) practitioner and researchers produced written reflections on PPI and (iv) sources one to three were consolidated during reflections that took place via e-mail and telephone correspondence between researchers and practitioners, culminating in a summary SKYPE meeting between one practitioner and one researcher involved in the PAGs. Results: Results in the form of reflections suggest guidelines on undertaking PPI were helpful with regard 'what to do', but less helpful on 'how'. For example, suggestions for the management of interpersonal factors such as eliciting self-disclosure and managing power differentials are insufficiently addressed in existing guidelines. Conclusions: The present case study illustrated how interpersonal considerations can help or hinder the optimal use of PPI. Recommendations for practitioners and researchers planning PPI are offered.